Edaravone dexborneol compared to edaravone in the treatment of acute cerebral infarction: A meta-analysis - Shi, Yanshuo; Yue, Yuanyuan; Wang, Mi; Wu, Huizhen (Frontiers in Pharmacology, 2025)
ObjectiveThe objective of this study was to systematically assess the clinical efficacy and safety of edaravone dexborneol compared to those of edaravone in treating acute cerebral infarction.MethodsWe searched the PubMed, Cochrane Library, Embase, CBM, CNKI, Wanfang Database, and VIP to gather randomized controlled trials (RCTs) comparing edaravone dexborneol with edaravone for treating acute cerebral infarction, covering studies from the database inception to February 2024. After data extraction and quality evaluation, a meta-analysis was carried out using RevMan 5.3 and Stada 18.0 statistical software.ResultsSeventeen RCTs were enrolled, including 2,778 patients, of which 1,493 and 1,285 were in the observation and control groups, respectively. The meta-analysis revealed that the total effective rate was significantly higher in the edaravone dexborneol group (RR = 1.17, 95% CI [1.11, 1.24], p < 0.00001) than in the edaravone group. Additionally, the rate of adverse reactions was significantly lower in the edaravone group (RR = 0.55, 95% CI [0.36, 0.82], p = 0.004). Fourteen days after treatment, the edaravone dexborneol group showed significantly better scores than the edaravone group in the NIHSS (MD = −2.13, 95% CI [-2.90, -1.35], p < 0.00001), Barthel Index (MD = 12.13, 95% CI [7.68, 16.58], p < 0.00001), and modified Rankin Scale (MD = −1.16, 95% CI [-1.75, -0.56], p = 0.0001).ConclusionEdaravone dexborneol demonstrates superior clinical efficacy and safety compared to edaravone in the treatment of acute cerebral infarction, suggesting it may be a more effective therapeutic option.